2011
DOI: 10.1038/mt.2011.132
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Proof-of-concept Clinical Trial With JX-594, a Targeted Multi-mechanistic Oncolytic Poxvirus, in Patients With Metastatic Melanoma

Abstract: JX-594 is a targeted and granulocyte macrophage-colony stimulating factor (GM-CSF)-expressing oncolytic poxvirus designed to selectively replicate in and destroy cancer cells through viral oncolysis and tumor-specific immunity. In order to study the mechanisms-of-action (MOA) of JX-594 in humans, a mechanistic proof-of-concept clinical trial was performed at a low dose equivalent to ≤10% of the maximum-tolerated dose (MTD) in other clinical trials. Ten patients with previously treated stage IV melanoma were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
94
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(100 citation statements)
references
References 27 publications
4
94
1
1
Order By: Relevance
“…As an example, we recently showed that a combination of SFV-IL-12 and a CD137 agonistic Ab can enhance antitumor immune responses against s.c. colon tumors in mice (33). In contrast, oncolytic viruses able to kill tumor cells in an immunogenic way showed very promising results in recent clinical trials (41,42). Based on both approaches, we believe that the combination of an SFV vector able to induce tumor cell death with a potent immunostimulatory cytokine, such as IL-12, and additional cytokines/factors able to enhance effector or memory immune responses or to inhibit suppressor responses could have a significant impact on cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, we recently showed that a combination of SFV-IL-12 and a CD137 agonistic Ab can enhance antitumor immune responses against s.c. colon tumors in mice (33). In contrast, oncolytic viruses able to kill tumor cells in an immunogenic way showed very promising results in recent clinical trials (41,42). Based on both approaches, we believe that the combination of an SFV vector able to induce tumor cell death with a potent immunostimulatory cytokine, such as IL-12, and additional cytokines/factors able to enhance effector or memory immune responses or to inhibit suppressor responses could have a significant impact on cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Extremely promising clinical trial data have recently emerged in which GM-CSF-armed vaccinia virus induced objective responses in patients with liver, colon, kidney, and lung cancer and melanoma (3,4). Vaccinia virus has several inherent features that make it particularly suitable for use as an oncolytic agent, including fast and efficient replication with rapid cell-to-cell spread, natural tropism for tumors, a well-documented safety record, and an ability to replicate in many different cell types, a feature not shared by adenoviruses.…”
Section: Introductionmentioning
confidence: 99%
“…The strategy improves cancer therapy through the dual action of the therapeutic gene and the oncolytic virus itself. The oncolytic poxvirus JX-594, which delivers granulocyte macrophage-colony stimulating factor (GM-CSF), exhibited outstanding antitumor results in a clinical trial via viral oncolysis and tumor-specific anti-cancer immunity [28] . JX-594 could selectively infect, replicate and express its transgene in cancer tissues but did not affect normal tissue; JX-594 was delivered into human metastatic solid tumors via intravenous infusion [29] .…”
Section: Discussionmentioning
confidence: 99%